Prevalence and Main Determinants of BRAF V600E Mutation in Dysplastic and Congenital Nevi - Maryam Nasimi; alireza Ghanadan; Kambiz Kamyab; vahidesadat Azhari; Tahereh Yousefi (Iranian Society of Pathology, 2021)
Background & Objective: Predicting the transformation of dysplastic or congenital nevi into malignant lesions results in a significant increase in the survival of patients. Some specific gene mutations have been reported to be very helpful in this regard. Therefore, this study aimed to evaluate the prevalence of BRAF V600E mutation in dysplastic and congenital nevi.Methods: This cross-sectional study was conducted on patients with congenital (n=30) or dysplastic (n=30) nevi. For genomic analysis, the BRAF gene mutation (V600E) was evaluated using the real-time polymerase chain reaction.Results: The prevalence of BRAF gene (V600E) mutation was found as 1 case (3.3%) in congenital and 8 cases (26.7%) in dysplastic nevi indicating the higher prevalence of this mutation in patients with dysplastic nevi (p =0.026). Moreover, in the dysplastic nevi group, the presence of BRAF gene mutation (V600E) showed  a significant relationship with the severity of dysplasia as the mutation rate was 25% in mild cases, in comparison with 54.5% in moderate dysplasia cases (p =0.009).Conclusion: According to the results, 3.3% of the patients with congenital nevi and 26.7% of the subjects with dysplastic nevi were positive for BRAF V600E mutation. Furthermore, the severity of dysplasia could have a positive relationship with the presence of the mutation.